Childhood Psychological Maltreatment, Aversion to Happiness and well-being in Young adults - Shakeel, Laiba; Saad, Maliha; Ayub, Sumaira (Journal of Postgraduate Medical Institute, 2025)
Objective: To explore the relationship among childhood psychological maltreatment, aversion to happiness, and subjective well-being in young adults, also to determine the role of childhood psychological maltreatment and aversion to happiness in predicting well-being. Methodology: A Correlational cross-sectional research design was used. The sample size comprised two hundred university students (N = 200) with an age range of 18 to 26 years old (M = 21.02, SD =1.59), including 84 men and 111 women. Data was collected from different universities in Lahore using self-constructed demographic information sheet and related scales. Data was analyzed using SPSS-26. Pearson product-moment correlation, multiple hierarchical regression, and t-test analyses to test the hypotheses. Results: The result illustrated that psychological maltreatment was positively related to aversion to happiness (r = .23, p<.01) and negatively related to well-being (r = -.29, p<.01) in young adults. Further, aversion to happiness was found to be negatively related (r = -.17, p<.05) to well-being among young adults. It was also found that psychological maltreatment significantly negatively predicted well-being (beta = -.25, p < .01); however, aversion to happiness did not predict it. The result also presented gender differences in terms of emotional well-being in men and women indicating higher scores in men, however, no gender differences were found in terms of childhood psychological maltreatment and aversion to happiness. Conclusion: It is concluded that childhood psychological maltreatment and aversion to happiness have a detrimental impact on the well-being of young adults.